Having: property and possession in religious and social life - Schweiker, William; Mathewes, Charles T. (Eerdmans, 2004)
The last few decades have witnessed the expansion of market economies into a complex global system. From shantytowns in Africa and rural villages around the Black Sea to the high-tech worlds of Tokyo, Berlin, and New York City, no place on the planet has escaped this development. While the present conditions of economic life are unique to our time, the human impulses that stand behind them are not. People have always negotiated life in economic terms, constituting much of their personal and social identity in relation to the things they possess.What, if anything, might religious studies and theological reflection contribute to thinking about and responding to the basic human reality of "having"? The engaging inquiries found in this volume provide some answers. Distinct from books taking purely economic, political, or social-scientific approaches to the subject, this book uses resources from the biblical traditions to throw fresh light on the role of property and possessions in cultural processes. Well-known scholars from a variety of fields (theology, ethics, economics, and biblical studies) explore in new and penetrating ways how people find value in having things, and how having things, in turn, gives value to social life. Their work will interest anyone grappling with issues of ownership and consumerism in today's global age.
Includes bibliographical references (p. 383-415)
Keywords: Konferenzschrift -- 2000 -- Chicago, Ill.; Bibel; Christliche Ethik; Besitz